9.3: Invited Paper: Geometric distortions in three‐dimensional endoscopic visualization. (4th October 2019) - Xia, Zhenping; Wang, Fei; Cheng, Cheng; Gu, Minming
Abstract : The three‐dimensional endoscope system is widely used for surgery and relative training of novice. The geometric distortions will affect the accuracy of size and distance estimation, and also may be one important factor inducing the visual discomfort. Based on the model of three‐dimensional endoscope image capture and display, the geometric distortions are analyzed. The results may provide some theoretical guidance for appropriate utilization of the three‐dimensional endoscope system.